1994
DOI: 10.1007/bf00058987
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-sprayed hydroxylapatite coating on carbon fibre reinforced thermoplastic composite materials

Abstract: Plasma-spraying of metallic implant surfaces is an established method for the application of hydroxylapatite (HA) coatings. Carbon fibre reinforced thermoplastics show different thermal and mechanical properties, compared with titanium substrates. In this paper first results of the influence of the established coating method on carbon fibre reinforced thermoplastics are presented. First investigations of the tensile adhesion strength, tested with a newly developed testing device, showed that the adhesion betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…Consequently, the study and modification of polymer interfaces, as opposed to composite engineering of the bulk biomaterial, is another active area of academic and commercial research involving PEEK. In an effort to improve the boneimplant interface, investigators have coated PEEK and PEEK composites with Ti alloy, as well as with hydroxyapatite (HA) [96,107]. Plasma deposition processing techniques are compatible with PEEK [96,108].…”
Section: Bioactive and Textured Surface Engineering Of Peek Implantsmentioning
confidence: 99%
“…Consequently, the study and modification of polymer interfaces, as opposed to composite engineering of the bulk biomaterial, is another active area of academic and commercial research involving PEEK. In an effort to improve the boneimplant interface, investigators have coated PEEK and PEEK composites with Ti alloy, as well as with hydroxyapatite (HA) [96,107]. Plasma deposition processing techniques are compatible with PEEK [96,108].…”
Section: Bioactive and Textured Surface Engineering Of Peek Implantsmentioning
confidence: 99%
“…15 This can be achieved in a number of ways, for example by applying coating with osteoconductive properties on the PEEK surface, such as with hydroxyapatite (HA). 10,[16][17][18] Due to its similarity to the mineral phase of natural bone tissue, artificial HA has been used over several decades as a bioactive coating material 19,20 and has been shown to have enhancing effects on osseointegration when coated onto implants. 21 There are several techniques for coating HA onto PEEK surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…21 There are several techniques for coating HA onto PEEK surfaces. For example, surface modifications have been performed through electron beam deposition of titanium, 22 plasma spray deposition of HA, 10 and spin coat deposition of a thin layer of nanocrystalline HA. 23 Some concern has been raised over the thickness of the HA coating and studies using thicker coatings of >10 mm have demonstrated complications with detachment of the coating from the bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…Studies had shown that when compared to Ti, PEEK stimulates less osteoblast differentiation. In an attempt to increase the osseoconductive properties of PEEK, it is coated and blended with bioactive particles . Various modifications had been done to enhance the surface characteristics of PEEK materials and to make it more biocompatible.…”
Section: Introductionmentioning
confidence: 99%